PEMBINAAN PENDIDIKAN KARAKTER MELALUI PROGRAM TAHFIDZUL QUR’AN DI MA MU’ALLIMAT KOTA MALANG - Awin Umiatul Chusnah; Abd Jalil; Imam Safi’i (VICRATINA, 2022)
This study aims to find out how character education is fostered through the TahfidzulQur'an Program at MA Mu'allimat Malang. This research uses descriptive qualitativemethods with data collection techniques in the form of documentation, observation,and interviews. The data collection techniques from this study are data reduction, datapresentation, and data verification. The results of this study explain that 1) Charactereducation development through the Tahfidzul Qur'an Program at MA Mu'allimatMalang is carried using of assistance by educators and through exemplary principles.2) Character education developed in the Tahfidzul Qur'an Program is packaged in theform of smoothing the reading, memorization and applying the Qur'an in everyday life.The inhibiting factors of the process of fostering character education through theTahfidzul Qur'an Program at MA Mu'allimat Malang are low self-awareness ofstudents and the influence of the environment or peers.